2012
DOI: 10.1021/jz3000036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Confined Water in Ionic Liquid Electrolytes for Dye-Sensitized Solar Cells

Abstract: Ionic liquids (ILs) provide an attractive medium for various chemical and redox reactions, where they are generally regarded as hydrophobic. However, Seddon et al. discovered that 4−10 wt % water absorbs into ILs that contain bulky anions, and Cammarata et al. found that the molecular state of water in ILs is dramatically different from that of bulk liquid water or that of water vapor. To determine the microstructure of water incorporated into ILs and the impact on properties, we carried out first-principlesba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 27 publications
1
40
0
2
Order By: Relevance
“…These ligands were exchanged with a thiol ligand (2–(dimethyl amino) ethane–thiol) and were dispersed in a conductive ionic liquid (1–ethyl–3–methylimidazolium bis (trifluromethylsulfonyl) imide) using the extraction process within solution phases as illustrated in the Supplementary Information (Figure S1a). The electrolyte was mixed with a proper combination of cation (EMIm–I or DMPII), anion (I 2 ), charge transport enhancer (LiI), recombination inhibitor (tBP), and water8. Then, the solution was directly injected into the DSSCs (Figure S1b).…”
Section: Resultsmentioning
confidence: 99%
“…These ligands were exchanged with a thiol ligand (2–(dimethyl amino) ethane–thiol) and were dispersed in a conductive ionic liquid (1–ethyl–3–methylimidazolium bis (trifluromethylsulfonyl) imide) using the extraction process within solution phases as illustrated in the Supplementary Information (Figure S1a). The electrolyte was mixed with a proper combination of cation (EMIm–I or DMPII), anion (I 2 ), charge transport enhancer (LiI), recombination inhibitor (tBP), and water8. Then, the solution was directly injected into the DSSCs (Figure S1b).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of water also remarkably affects the surface structure of ILs, such as the number and orientation of ions at the surface, which further change the surface tension of the ILs . However, it was reported that the presence of water in ILs can promote the diffusion of redox species and increase the corrosion rate of alloys . Most importantly, a small amount of water could possibly change the structure of the electric double layer (EDL) and thus the kinetic parameters of electroactive species at the electrochemical interface .…”
Section: Introductionmentioning
confidence: 99%
“…I -may also assist the current flow. In such cases, rapid charge transfer is enabled even in a viscous medium, as physical transfer of species is not necessary for charge transport [42][43][44].…”
Section: Electrochemical Behaviormentioning
confidence: 99%